Pengaruh Senam Hamil terhadap Kualitas Tidur Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Ratu Agung Kota Bengkulu - Tria Nopi Herdiani; Arta Uli Simatupang (Journal for Quality in Women's Health, 2019)
Sleep disturbances are experienced in pregnant women, especially in the third trimester of pregnancy. Sleep difficulties in pregnant women can be a reduction in sleep duration of pregnant women. Efforts to overcome these sleep difficulties include sports, namely pregnancy exercise. One of the benefits of pregnancy exercise regularly and measurably is to improve the quality of sleep and master breathing techniques and can set yourself up to calm. The purpose of this study was to study the effect of pregnancy exercise on the quality of sleep in pregnant women in the third trimester in the work area of ​​Ratu Agung Health Center in Bengkulu City in 2018.